2013
DOI: 10.1007/s00216-013-7171-z
|View full text |Cite
|
Sign up to set email alerts
|

Analytical determination of specific 4,4′-methylene diphenyl diisocyanate hemoglobin adducts in human blood

Abstract: 4,4'-Methylene diphenyl diisocyanate (MDI) is one of the most important isocyanates in the industrial production of polyurethane and other MDI-based synthetics. Because of its high reactivity, it is known as a sensitizing agent, caused by protein adducts. Analysis of MDI is routinely done by determination of the nonspecific 4,4'-methylenedianiline as a marker for MDI exposure in urine and blood. Since several publications have reported specific adducts of MDI and albumin or hemoglobin, more information about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Groups have investigated 4,4′-MDI-hemoglobin adducts at the N-terminal valine [14] . Gries and Leng validated a method that measured hydantoin adducts levels in plasma which formed following acid treatment of 4,4′-MDI conjugated to the N-terminal amino acid [15] . Sufficient sensitivity was achieved to quantify the possible adduct levels, however poor analyte recoveries were observed following 2 M HCl hydrolysis (2 h at 80 °C) and solid phase extraction (SPE) cleanup of the biological samples (or spiked matrix samples).…”
Section: Introductionmentioning
confidence: 99%
“…Groups have investigated 4,4′-MDI-hemoglobin adducts at the N-terminal valine [14] . Gries and Leng validated a method that measured hydantoin adducts levels in plasma which formed following acid treatment of 4,4′-MDI conjugated to the N-terminal amino acid [15] . Sufficient sensitivity was achieved to quantify the possible adduct levels, however poor analyte recoveries were observed following 2 M HCl hydrolysis (2 h at 80 °C) and solid phase extraction (SPE) cleanup of the biological samples (or spiked matrix samples).…”
Section: Introductionmentioning
confidence: 99%
“…Isocyanates are known to react with endogenous substances (Sabbioni et al, 2010;Gries and Leng, 2013), and MDI in particular has demonstrated reactivity with GSH (Wisnewski et al, 2013). The chemical reactivity of MDI is considered responsible for its toxicity to cells (Wisnewski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have indicated that the chemical reactivity of MDI with endogenous substances such as albumin and glutathione (GSH) is responsible for its allergenic properties. Isocyanate-specific adducts of MDI with hemoglobin and albumin are involved in the etiology of the sensitization reaction (Sabbioni et al, 2010;Gries and Leng, 2013). MDI reactivity with GSH releases byproducts that stimulate pathogenic inflammatory processes such as macrophage activation and eosinophilic airway inflammation (Wisnewski et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the mentioned above problems and possibility of additional skin adsorption of DIC, biological monitoring seems to be a better way for occupational exposure assessment or for identification of susceptible subjects among the exposed workers. At present, biological monitoring of exposure to isocyanates is carried out based on the measurement of concentrations of the corresponding amines (4,4'-methylenedianiline -MDA, 2,4-toluenediamine -2,4-TDA, 2,6-toluenediamine -2,6-TDA and 1,6-hexanediamine -HDA) [12][13][14][15][16][17][18][19][20][21][22][23] in urine or determination of the ad ducts of diisocyanates with hemoglobin or albumin in blood [14,[24][25][26][27]. Also the presence of specific immunoglobulin E (IgE) antibodies in serum is suggested as an indicator of exposure to diisocyanates [28].…”
mentioning
confidence: 99%